2013
DOI: 10.1186/1471-2334-13-67
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of chikungunya seropositivity in healthy Malaysian adults residing in outbreak-free locations: Chikungunya seroprevalence results from the Malaysian Cohort

Abstract: BackgroundIn 1998, Malaysia experienced its first chikungunya virus (CHIKV) outbreak in the suburban areas followed by another two in 2006 (rural areas) and 2008 (urban areas), respectively. Nevertheless, there is still a lack of documented data regarding the magnitude of CHIKV exposure in the Malaysian population. The aim of this study was to determine the extent of chikungunya virus infection in healthy Malaysian adults residing in outbreak-free locations.MethodsA cross sectional study of chikungunya (CHIK) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 16 publications
(23 reference statements)
3
32
2
Order By: Relevance
“…In comparison to neighboring Malaysia, the CHIKV seroprevalence in this study is higher than that reported among healthy Malaysian adults ≥35 years old (5.9%) residing in outbreak-free areas [30]. In contrast, regional DENV seroprevalence rates have been comparable.…”
Section: Discussioncontrasting
confidence: 71%
“…In comparison to neighboring Malaysia, the CHIKV seroprevalence in this study is higher than that reported among healthy Malaysian adults ≥35 years old (5.9%) residing in outbreak-free areas [30]. In contrast, regional DENV seroprevalence rates have been comparable.…”
Section: Discussioncontrasting
confidence: 71%
“…Persistent vector populations and naïve populations contributed to notable pre-2000 CHIKV outbreaks in India, Myanmar/Burma, Philippines, Sri Lanka, Thailand and Vietnam [35,36]. In the last decade, outbreaks have been reported in India, Indian Ocean islands, Indonesia, Sri Lanka, and Thailand, following a 41-year period of quiescence [37,38]. Good to better consensus on CHIKV presence was reported for 80% of Asian countries and clusters of complete consensus were observed ranging from Myanmar/Burma to Vietnam for south Asia and Indonesia to Papua New Guinea for south-east Asian islands (Figure 5a).…”
Section: Resultsmentioning
confidence: 99%
“…In some studies, men appeared to be more susceptible to dengue infection whereas in others, women were more affected, and no gender differences were noted in others. This inconsistency may relate to gender differences in exposure to infection due to community-specific habits, customs or behaviours (Sissoko et al, 2008 andAzami et al, 2013).…”
Section: Resultsmentioning
confidence: 99%